1979
DOI: 10.1677/joe.0.0830219
|View full text |Cite
|
Sign up to set email alerts
|

Stimulation of Cartilage Zones of the Calf Costochondral Growth Plate in Vitro by Growth Hormone Dependent Rat Plasma Somatomedin Activity

Abstract: The actions of rat plasma somatomedin activity dependent on growth hormone were investigated in vitro on separated zones of cartilage from the calf costochondral junction. Plasma somatomedin maximally stimulated the uptake of[3H]thymidine into cartilage cells of the proliferating region. Cartilage deeper in the growth plate possessed the highest uptake of [35S]sulphate which was also stimulated by somatomedin. Somatomedin, therefore, appears to promote both cell replication and matrix synthesis throughout the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
20
0

Year Published

1980
1980
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(24 citation statements)
references
References 14 publications
4
20
0
Order By: Relevance
“…This finding confirms the results of other investigators (6,7), who were unable to demonstrate direct effects ofgrowth hormone in different in vitro systems and clearly shows that growth hormone has no direct mitogenic effect on isolated chondrocytes. The observed increase oftibial width after local injection of growth hormone in hypophysectomized rats and the increased DNA and matrix synthesis in high density chondrocyte culture indicate that a possible direct action of growth hormone needs a special microenvironment which in itself might provide mediators for its action (8)(9)(10).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…This finding confirms the results of other investigators (6,7), who were unable to demonstrate direct effects ofgrowth hormone in different in vitro systems and clearly shows that growth hormone has no direct mitogenic effect on isolated chondrocytes. The observed increase oftibial width after local injection of growth hormone in hypophysectomized rats and the increased DNA and matrix synthesis in high density chondrocyte culture indicate that a possible direct action of growth hormone needs a special microenvironment which in itself might provide mediators for its action (8)(9)(10).…”
Section: Discussionsupporting
confidence: 92%
“…The stimulatory effects of hormones and growth factors on human skeletal growth can be assessed in an in vitro culture system that measures the proliferation of single chondrocytes to cell clones in a semisolid medium (2 (6,7). Recently, Isaksson (8) reported that GH injected locally into epiphyseal growth plates of hypophysectomized rats leads to a significant increase of growth plate width.…”
Section: Introductionmentioning
confidence: 99%
“…This finding is supported by analogous data in vitro pertaining to osteoblast (37) and preadipocyte differentiation (38). Experiments using cultured growth plate chondrocytes have yielded conflicting results in this respect: some studies describe IGF-I acting selectively on the differentiated proliferating cell pool (5), whereas others report that all stages of Figure S growth plate cell differentiation are responsive to this hormone, although to a varying degree (39)(40)(41). Moreover, contrary to general belief, the effects of IGF-I at the proliferative phase of activity are exerted primarily by a shortening of the cycle time rather than by clonal expansion, i.e., by increasing the cell pool size.…”
Section: Methodsmentioning
confidence: 99%
“…These short fiber/branchedclusters could potentially be used as spacers in pellet culture to mimic the lower cell densities of native cartilage. The modular nature of these fibers/clusters could potentially allow for more tailorability of the matrix, with chondrocytes rearranging them according to the arrangements of fibers found in the various zones of native cartilage [39,40]. Chondrocytes could be isolated from cartilage taken from patients, combined with fibers/clusters to create cartilage analogs which could be strengthened in a cyclic compression bioreactor, and then re-implanted into the patient.…”
Section: Figurementioning
confidence: 99%